Protection & assistance for all in the face of disasters in the 21st century : World Action Plan for the Development of Civil Protection (International Civil Defence Organization GenevaCH, 1998)
Presents the Beijing Declaration and the world Action Plan for the Development of Civil Protection Structures.
Keywords: DISASTERS